Recent research in nutrition and growth - Arner, Peter; Bhutta, Zulfiqar Ahmed 1955-; Black, Maureen M.; Black, Robert E.; Carlson, Susan E.; Colombo, John; Koletzko, Berthold 1954-; Lampl, Michelle Leigh (Nestlé Nutrition Institute workshop series, 2018)
As nutrition and development are closely intertwined in early childhood, this book brings together scientists, nutritionists, and psychologists to present a multidisciplinary approach. The first part examines how the biological systems of the body may contribute to healthy growth, looking at bones, muscles, and fat tissues and the optimal nutrition required for dynamic function. The second section contains updates on the latest research on dietary interventions in the areas of growth and body composition, looking at both obesity and stunting worldwide. The final part focuses on neurocognitive development in infancy and early childhood and the role of nutrients in supporting brain growth and function. Highlighting key areas of recent research and potential new fields to explore, this book is of interest for scientists, nutritionists, and psychologists alike.